The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/jhq.0000000000000252
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Level Predictors of Discharges Against Medical Advice: Identifying Contributors to Variation Using an All-Payer Database

Abstract: There is increasing evidence of the role of non–patient-level factors on discharge against medical advice (DAMA), but limited quantitative information regarding the extent of their impact. This study quantifies the contribution of discharge-level and hospital-level factors to the variation in DAMA. We grouped variables from the 2014 National Inpatient Sample data and ran incremental mixed-effects logit models with grouping at the level of the discharge, the hospital, and the census region. We obtained the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…First, these findings add to evidence that a non-patient-level factor may be associated with DAMA and play a role in its increasing prevalence over time. Previous studies have identified other non-patient-level factors that are associated with DAMA, including a hospital's quality metrics, 39 location, 40 and teaching status. 41 Our findings may be relevant in the design of system-level interventions to reduce DAMA, including policy changes.…”
Section: Discussionmentioning
confidence: 99%
“…First, these findings add to evidence that a non-patient-level factor may be associated with DAMA and play a role in its increasing prevalence over time. Previous studies have identified other non-patient-level factors that are associated with DAMA, including a hospital's quality metrics, 39 location, 40 and teaching status. 41 Our findings may be relevant in the design of system-level interventions to reduce DAMA, including policy changes.…”
Section: Discussionmentioning
confidence: 99%
“…Experts emphasize that unplanned discharge is a system-level problem that cannot be solely attributed to behaviors or characteristics of individual patients (Alfandre, 2019; White et al, 2005). This concern has been borne out in the literature where studies have found that rates of AMA discharge vary based on hospital characteristics such as urban location, medium hospital size, and for-profit status (Onukwugha et al, 2021). Available studies, however, have generally focused their attention on acute medical wards and have not considered whether unplanned discharge rates also vary based on mental health treatment settings including acute inpatient and residential settings.…”
mentioning
confidence: 99%